Erratum to: Cirrhilabrus cyanogularis, a new species of fairy wrasse from the Philippines and Indonesia (Teleostei: Labridae) - Tea, Yi-Kai; Frable, Benjamin W.; Gill, Anthony C. (Zootaxa, 2018)
Following publication of the original article (Tea et al., 2018), an error was noted in the museum registration number for the holotype of the new species Cirrhilabrus cyanogularis (PNM 15354). This registration number is a duplicate number already in use for the holotype of Cirrhilabrus shutmani (Tea & Gill, 2017). The new registration number for the holotype of Cirrhilabrus cyanogularis is now PNM 15360.